Purrankia (Opiliones: Laniatores: Gonyleptidae), a new genus of Pachylinae from the Coastal Range of southern Chile, with descriptions of three new species - Pérez-Schultheiss, Jorge; Silva-Ahumada, Benjamín; Toledo-Araneda, Marisol (Zootaxa, 2026)
Three new species of the Chilean endemic genus Purrankia gen. nov. are described based on specimens obtained in the Coastal Range of the Los Ríos and Los Lagos region. The new genus is distinctive morphologically, due to its swollen body, the apophyses on the lateral margin of the mesotergum, the structure of the apophyses on trochanter IV and the short femur. Morphological and molecular information suggests relationships with the genus Fonckia Roewer, 1913 and Eubalta Roewer, 1923, with which it shares a series of characteristics, including the unarmed ocularium and frontal hump, the short distal prolateral apophysis of coxa IV, the structure of trochanter IV and the male genitalia. The three newly described species have allopatric distributions, always associated with low to medium altitudes on both slopes of the Coastal Range. Purrankia manquemapu sp. nov., is present on the western slope of the Coastal Range in the commune of Purranque (Los Lagos Region, Chile), while Purrankia hueyusca sp. nov. inhabits the eastern slope in the same area. The third species, Purrankia oncol sp. nov., has the northernmost distribution, being found in Oncol Park, in the Los Ríos region. Detailed descriptions, illustrations and comparisons of each of the new species and a phylogenetic hypothesis based on mitochondrial COI data are provided.